Antitubercular activity of silver(I) complexes with 7-chloro-4-aminoquinolines: synthesis, characterization and in vitro biological assays - D’Oliveira, Kaíque A.; Souza, Isabela O.; Glanzmann, Nícolas; Da Silva, Adilson D.; Bruziguini, Carlos E. T.; Ribeiro, Marcos A.; Canales, Christian S. C. [UNESP]; Roque-Borda, Cesar A. [UNESP]; Pavan, Fernando R. [UNESP]; Cuin, Alexandre (Taylor & Francis, 2025)
This article describes the synthesis, characterization, and biological activity of four quinoline derivatives, ACQ12, ACQ13, ACQ14, ACQophen, and their respective silver(I) complexes. The organic compounds are composed of 4,7-dichloroquinoline derivatives containing aliphatic diamines, 1,2-ethanediamine (ACQ12), 1,3-propanediamine (ACQ13), 1,4-butanediamine (ACQ14), and an aromatic diamine, o-phenylenediamine (ACQophen), as a side chain at the 4-position of the quinoline ring. The crystalline structure of ACQophen was solved by single crystal X-ray diffraction, while the crystal structures of Ag-ACQ12 (1), Ag-ACQ13 (2), Ag-ACQ14 (3), and Ag-ACQophen (4) were obtained by polycrystals X-ray diffraction technique. Silver complexes have shown a 1:1 (M:L) molar ratio. Further characterization in all compounds was performed by analytical methods and spectroscopic techniques. Elemental analyses, conductometry and IR, Raman and UV–Vis spectroscopies confirmed the proposed molecular formulas. Coordination occurs through the nitrogen atom of the quinoline ring. Biological assays in vitro were performed for all synthesized compounds against Mycobacterium tuberculosis H37Rv American Type Collection Culture 27294 (ATCC 27294). Free aminoquinolines and 3 and 4 showed MIC90 below 13.0 mg L−1. The ACQophen showed selectivity index (SI) over 190 and its Ag(I) complex has SI = 3.09, making these compounds promising antimycobacterial agents.
Keywords: 7-Chloro-4-aminoquinolines; Mycobacterium tuberculosis; silver(I) complexes